Arts of allusion object, ornament, and architecture in medieval Islam - Graves, Margaret S. (Oxford University Press, 2018)
Through close studies of ceramics, metalwares and other plastic arts from the ninth to the thirteenth centuries, Arts of Allusion reveals the object as a crucial site where pre-modern craftsmen of the eastern Mediterranean and Persianate realms engaged in fertile dialogue with poetry, literature, painting, and, most strikingly, architecture